Application of Prospective Analysis and Cluster Analysis as a Tool to Aid in the Design of Rural Development Policies: the Case of Andalusia - PEREZ HERNANDEZ, PEDRO PABLO; UNIVERSIDAD LOYOLA ANDALUCIA (2014)
The EU has promoted initiatives to develop its rural areas. In this research, we apply the last of those initiatives to Andalusia (southern Spain). These are the main aims pursued in this study: first, to present the methodology selected to identify the most influential variables that act as catalysts for development in each rural county of Andalusia; second, to identify rural county groups that show basic similarities in terms of the variables selected and third, to contribute to the integration of development strategies. To reach those objectives, it was applied the Prospective Structural Analysis as well as Cluster Analysis along with Discriminant Analysis to validate it. The results show the existence of four clearly differentiated clusters in the region.